Planning Policies and Strategies Implementation Effects on Accelerated Development in The Pesisir Barat Regency, Lampung Province - Muttaqin, Muttaqin; Supriyatno, Budi; Rahimullah, Rahimullah (Ridwan Institute, 2023)
This study aims to analyze the effect of the implementation of policies and planning strategies on the acceleration of development in the Pesisir Barat Regency, Lampung Province, by looking at how the implementation of policies is linked to the implementation of policies and planning strategies with the acceleration of development in the Pesisir Barat Regency, Lampung Province. In addition, the research is limited to the object of research, namely in the Pesisir Barat Regency, Lampung Province. This study uses a quantitative method with explanatory research type, with a population of 98 and a research sample of 49 people determined by the Slovin formula. The data collection technique in this research is the questionnaire and library techniques. The research hypothesis proves that there is a significant and positive influence on the Implementation of Planning Policies and Strategies on the Acceleration of Development. Based on the results of the study, it can be concluded that there is a significant and positive effect of Policy Implementation on the Acceleration of Development of 97.1% and there is a significant and positive influence of Planning Strategy on the Acceleration of Development of 90.5%, where together there is a significant and positive effect of motivation. and the provision of compensation for employee performance by 97.2% with the dominant indicators of accelerated development being attention, responsibility and action programs from strategies in the Acceleration of Development in Pesisir Barat Regency - Lampung Province.